Efektivitas Pemberian Challenging Mathematical Task Terhadap Higher Order Thinking Skills (Hots) Siswa Sekolah Dasar - Rohimatul Hayati; Hepsi Nidiasari (Journal on Education, 2023)
This study aims to examine the effectiveness of challenging mathematical tasks on the higher order thinking skills of elementary school students. The research design employed is a pre-experimental approach utilizing a one-group pretest-posttest design. The intervention applied in this study involves implementing challenging mathematical tasks in teaching the topic of fractions in mathematics. The research was conducted at SD Unggulan Uswatun Hasanah Cilegon, involving a study sample of 21 fourth-grade students from Class IV Al Farghani. Prior to the intervention, the students were administered a pretest, followed by a posttest after the intervention. Analysis of the improvement in higher order thinking skills utilized the T-Test and N-Gain formulas. The T-Test was used to determine the significance of the improvement in higher order thinking skills, while the N-Gain measured the magnitude of this enhancement. Based on the N-Gain analysis, a notably higher improvement in higher order thinking skills was observed, indicating a difference between the pretest and posttest scores. The results of the Paired Sample T-Test demonstrated a significant influence, suggesting an enhancement in learning outcomes in the posttest.